NARRATIVE ANALYSIS OF FAMILY COMMUNICATION THROUGH THE STORY STRUCTURE OF THE MOVIE "BILA ESOK IBU TIADA" - April Yana; Muhammad Husni Ritonga (Journal Analytica Islamica, 2026)
This study analyzes family communication in the film *Bila Esok Ibu Tiada* through the lens of Tzvetan Todorov’s narrative structure theory. The primary focus of this study is to understand how family communication is constructed and influenced by emotional conflicts, particularly between mother and child, as depicted in the film. This study identifies five narrative stages in the film: initial equilibrium, disruption, recognition of the disruption, attempt to repair, and new equilibrium. Each stage is analyzed to examine how the dynamics of family Communication are manifested through the plot, conflict, and resolution. The results indicate that Todorov’s narrative structure is effective in depicting changes in family communication, particularly within the context of mother-child relationships influenced by dramatic events within the family. This study makes a new contribution to communication studies by integrating Todorov’s narrative theory into the analysis of family communication in film. Thus, this study not only enriches the field of family communication research but also offers a new approach to analyzing film as a narrative text.